Serum ferritin as a prognostic biomarker in CAR-T therapy for multiple myeloma: A meta-analysis - Jing Cheng; Yuan Song (Biomolecules & Biomedicine)
Serum ferritin, a marker of systemic inflammation and iron metabolism, has been implicated in the outcomes of patients with relapsed/refractory multiple myeloma (R/R MM). However, its prognostic significance in R/R MM patients undergoing chimeric antigen receptor-modified T-cell (CAR-T) therapy remains unclear. This meta-analysis aimed to evaluate the association between pre-infusion serum ferritin levels and survival outcomes in R/R MM patients treated with CAR-T therapy. We systematically searched PubMed, Embase, and Web of Science for relevant studies. Studies reporting progression-free survival (PFS) and/or overall survival (OS) based on serum ferritin levels were included. Hazard ratios (HRs) with 95% confidence intervals (CIs) were pooled using a random-effects model. Eight retrospective cohort studies, encompassing 1,077 patients, met the inclusion criteria. High pre-infusion serum ferritin levels were significantly associated with worse PFS (HR: 2.15, 95% CI: 1.74–2.66, p < 0.001) and OS (HR: 2.86, 95% CI: 2.20–3.72, p < 0.001), with mild heterogeneity (I² = 9% for PFS and 0% for OS). Sensitivity analyses, conducted by excluding one study at a time, confirmed the robustness of these findings. Subgroup analyses showed consistent results across different CAR-T product sources (commercial vs. academic), ferritin cutoffs, and follow-up durations (p for subgroup differences all > 0.05). In conclusion, elevated serum ferritin levels before CAR-T infusion predict poorer survival outcomes in R/R MM patients. These findings highlight the potential prognostic value of ferritin and its role in optimizing patient selection and management strategies in CAR-T therapy.